Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18189902
|View full text |Cite
|
Sign up to set email alerts
|

Defining Adjustment to Address the Missing Link between Refugees and Their Resettlement Communities

Abstract: Background: data from the United Nations High Commissioner for Refugees (UNHCR) show that, in 2020, among 82.4 million refugees, only 251,000 returned to their home countries, indicating the desire for refugees to stay, for the long-term, in their new homelands. The paper contributes to the scientific–psychological debate on the social representation of refugee populations, by studying this population, not simply as “foreigners”, traumatized and resourceless people, but rather focusing on the factors that lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Studies demonstrate social support provides a buffer against psychological distress and various disorders [48,49]. In addition to social support, 28.3% of the studies in the review noted building and strengthening community networks was beneficial for psychological wellbeing, life satisfaction, and resettlement [20,27,34,45,47,50,51]. Notably, Remennick's work [52,53] and Tippens et al [24] demonstrate how support from co-ethnic communities significantly boosts the psychological well-being and health of older women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies demonstrate social support provides a buffer against psychological distress and various disorders [48,49]. In addition to social support, 28.3% of the studies in the review noted building and strengthening community networks was beneficial for psychological wellbeing, life satisfaction, and resettlement [20,27,34,45,47,50,51]. Notably, Remennick's work [52,53] and Tippens et al [24] demonstrate how support from co-ethnic communities significantly boosts the psychological well-being and health of older women.…”
Section: Discussionmentioning
confidence: 98%
“…One of the eligible studies analysed differences between migrant and non-migrant groups. Across 40 studies, the sample sizes ranged from 2 to 5678 participants (N = 80,265), with the exclusion of three studies [20][21][22] as they reported only the number of articles, not participant counts. The sample sizes of the quantitative studies ranged from 50 to 5678 participants, with a total of 16,189 participants.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…Applications of sense of community theory to health research have become more prominent in studies examining the roles of social capital, social networks, and social cohesion on health and healthcare delivery (e.g., Carpiano & Hystad, 2011; Hystad & Carpiano, 2010; Mahmoudi Farahani, 2016). Sense of community theory has also been used by researchers exploring immigrant and refugee postmigration adjustment (Badali et al, 2017; Keel & Drew, 2004; Modesti & Talamo, 2021; Weng & Lee, 2016). Weng and Lee (2016) noted the importance of ethnic community in cultural maintenance and in extending familial and fictive kin networks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although such adversities present true risks, they do not necessarily predestine refugees to adverse outcomes. In fact, many refugees show signs of positive adjustment and some even show signs of flourishing following resettlement, which may indicate the presence of resilience or protective factors [5][6][7]. Although much research in this area adopts a lens of risk, there are growing calls to better understand and nurture the unique strengths of refugees [8,9].…”
Section: Introductionmentioning
confidence: 99%